2010
DOI: 10.1677/erc-10-0059
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear androgen receptor staining in bone metastases is related to a poor outcome in prostate cancer patients

Abstract: Androgen receptors (ARs) are probably of importance during all phases of prostate cancer (PC) growth, but their role in bone metastases is largely unexplored. Bone metastases were therefore collected from hormone-naive (nZ11), short-term castrated (nZ7) and castration-resistant PC (CRPC, nZ44) patients by biopsy (nZ4) or at surgery to alleviate symptoms from metastases complications (metastasis surgery, nZ58), and immunostained for nuclear ARs, Ki67, active caspase-3, prostate-specific antigen (PSA) and chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 31 publications
2
66
0
Order By: Relevance
“…In human PCa patients, 90% of PCa metastases occur in bone[35], and the majority have strong expression of nuclear AR[158]. In the limited GEM models that develop metastatic bone lesions, the penetrance varies from “rare” up to about 17%.…”
Section: Discussionmentioning
confidence: 99%
“…In human PCa patients, 90% of PCa metastases occur in bone[35], and the majority have strong expression of nuclear AR[158]. In the limited GEM models that develop metastatic bone lesions, the penetrance varies from “rare” up to about 17%.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Since AR overexpression is a late event in the progression of prostate cancer, AR is a potential marker for metastatic prostate cancer. Crnalic et al 22 showed that only two cases out of 58 investigated bone metastases were negative for AR. Concordant with these findings, we also observed a high-expression frequency for AR in distant metastases (91%).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity also extends to the distribution and intensity of AR expression, as revealed by immunohistochemical studies of CRPC bone metastases 88, 90–92 . For example, in a study with 44 CRPC bone metastases, 58.1% of patients had moderate (30.4% of cases) to intense (69.6% of cases) AR staining in 76–100% of the tumor cells, whereas 8.8% of the patients in the study had AR staining in just 1–25% of tumor cells 92 . Thus, metastatic CRPC can exist as a mixture of cells displaying a range of AR expression levels.…”
Section: Complete Androgen Receptor Independencementioning
confidence: 92%